2013
DOI: 10.3390/molecules18089021
|View full text |Cite
|
Sign up to set email alerts
|

Solid-, Solution-, and Gas-state NMR Monitoring of 13C-Cellulose Degradation in an Anaerobic Microbial Ecosystem

Abstract: Anaerobic digestion of biomacromolecules in various microbial ecosystems is influenced by the variations in types, qualities, and quantities of chemical components. Nuclear magnetic resonance (NMR) spectroscopy is a powerful tool for characterizing the degradation of solids to gases in anaerobic digestion processes. Here we describe a characterization strategy using NMR spectroscopy for targeting the input solid insoluble biomass, catabolized soluble metabolites, and produced gases. C-labeled cellulose produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…These results indicate that 13 C-acetic acid and -propionic acid were metabolized and synthesized by Clostridia and Mollicutes. Using correlation analysis, we previously demonstrated that the levels of 13 C-acetic acid and -propionic acid increased as cellulose was degraded, suggesting that the generation of 13 C-labeled organic acids was caused by the anaerobic digestion of 13 C-cellulose [5]. Considering our current findings, we suggest that 13 C-BC was digested by clostridial species and Mollicutes accompanied by the production of acetic acid and propionic acid in the anaerobic microbial ecosystem.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…These results indicate that 13 C-acetic acid and -propionic acid were metabolized and synthesized by Clostridia and Mollicutes. Using correlation analysis, we previously demonstrated that the levels of 13 C-acetic acid and -propionic acid increased as cellulose was degraded, suggesting that the generation of 13 C-labeled organic acids was caused by the anaerobic digestion of 13 C-cellulose [5]. Considering our current findings, we suggest that 13 C-BC was digested by clostridial species and Mollicutes accompanied by the production of acetic acid and propionic acid in the anaerobic microbial ecosystem.…”
Section: Resultssupporting
confidence: 59%
“…Solution-state NMR data were reduced by subdividing the spectra and were processed and normalized for statistical analysis, as described previously [5]. PCA of the binned data was performed using “R” software according to a previous study [48].…”
Section: Methodsmentioning
confidence: 99%
“…The extracted samples were measured on an AVANCE II 700 spectrometer (Bruker BioSpin GmbH, Rheinstetten, Germany). The 1 H-NMR spectra were observed using a Bruker standard pulse program "p3919gp" with solvent suppression by the WATERGATE sequence [29,30]. A 90 • pulse angle was used, and the spectral parameters for the large-scale dataset were as follows: number of data points, 32 k; spectral width, 9804 Hz; acquisition time, 1.67 s; delay time, 2.5 s; and number of scans, 64.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…MNR also provides accurate quantification 10 with inter-institution convertibility 11 . In previous studies, NMR-based metabolic profiling has been applied to plants [12][13][14][15] , animals [16][17][18][19][20] , and microbial [21][22][23][24] systems.…”
Section: Introduction * Junkikuchi@rikenjpmentioning
confidence: 99%